An overview of proximal suspensory ligament desmitis. (2nd September 2019) - Anderson, Jonathan
Abstract : Proximal suspensory disease is a common cause of both forelimb and hindlimb lameness and poor performance in the horse. The following article describes the common presentations, diagnostic techniques and treatment options for the condition in both the forelimbs and the hindlimbs.